2013
DOI: 10.1111/j.1540-4781.2013.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Use of Captions by Foreign Language Learners: An Eye‐Tracking Study

Abstract: This study investigates caption‐reading behavior by foreign language (L2) learners and, through eye‐tracking methodology, explores the extent to which the relationship between the native and target language affects that behavior. Second‐year (4th semester) English‐speaking learners of Arabic, Chinese, Russian, and Spanish watched 2 videos differing in content familiarity, each dubbed and captioned in the target language. Results indicated that time spent on captions differed significantly by language: Arabic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 99 publications
(186 reference statements)
4
109
1
2
Order By: Relevance
“…These null findings contradict two lines of research, one showing beneficial effects of subtitles, the other showing detrimental effects. Earlier research which has shown beneficial effects of subtitles are primarily studies on second language learning, which show that 2 nd language subtitles help students with learning that language (e.g., Baltova, 1999;Chung, 1999;Markham, 1999;Winke et al, 2013). While this appears conflicting with the results of the present study, the important difference is that the current study did not use language learning videos but 'content' videos, and did not measure gains in 2 nd language proficiency.…”
Section: No Main Effect Of Subtitlescontrasting
confidence: 56%
See 1 more Smart Citation
“…These null findings contradict two lines of research, one showing beneficial effects of subtitles, the other showing detrimental effects. Earlier research which has shown beneficial effects of subtitles are primarily studies on second language learning, which show that 2 nd language subtitles help students with learning that language (e.g., Baltova, 1999;Chung, 1999;Markham, 1999;Winke et al, 2013). While this appears conflicting with the results of the present study, the important difference is that the current study did not use language learning videos but 'content' videos, and did not measure gains in 2 nd language proficiency.…”
Section: No Main Effect Of Subtitlescontrasting
confidence: 56%
“…Specifically, enabling subtitles for language learning videos substantially increases student performance on recognition tests, and to a lesser extent on production tests. Other studies have found similar positive effects of subtitles on learning from videos and there appears to be a consensus that subtitles are beneficial for learning a second language (e.g., Baltova, 1999;Chung, 1999;Markham, 1999;Winke, Gass, & Sydorenko, 2013). However, these are all studies which focus on learning a language and not on learning about a non-linguistic topic in a second language.…”
Section: Subtitles: Beneficial or Detrimental For Learning?mentioning
confidence: 83%
“…Test announcement has indeed been found to correlate with participants' better performance on tests. Winke, Gass, and Sydorenko (2013) found that their participants in the test announcement condition using full captioning or keyword captioning performed better than participants who did not receive a test announcement before watching the video in those conditions. The authors posit that test announcement possibly prompted them to reanalyze the content of the subtitles more closely, thus spending additional time on the subtitles area to process it more effortfully and therefore gather more information to understand the narration.…”
Section: Discussionmentioning
confidence: 99%
“…Markham, Peter, and McCarthy's (2001) revealed that participants' level of recall of the video content was much lower when no subtitles were available than when they were for non-familiar material, that is, for video materials with which participants were not so familiar in terms of content/genre. Also, Winke, Gass, and Sydorenko's (2013) eye-tracking study demonstrated that video content familiarity correlated with the type of L2 being learned, which, in that case, was Chinese, a language that required more processing of subtitles with a video that was deemed more difficult for the kind of topic it portrayed, being unfamiliar to the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation